Coordination among tertiary base pairs results in an efficient frameshift-stimulating RNA pseudoknot. Issue 10 (21st February 2017) - Chen, Yu-Ting; Chang, Kai-Chun; Hu, Hao-Teng; Chen, Yi-Lan; Lin, You-Hsin; Hsu, Chiung-Fang; Chang, Cheng-Fu; Chang, Kung-Yao; Wen, Jin-Der
Abstract: Frameshifting is an essential process that regulates protein synthesis in many viruses. The ribosome may slip backward when encountering a frameshift motif on the messenger RNA, which usually contains a pseudoknot structure involving tertiary base pair interactions. Due to the lack of detailed molecular explanations, previous studies investigating which features of the pseudoknot are important to stimulate frameshifting have presented diverse conclusions. Here we constructed a bimolecular pseudoknot to dissect the interior tertiary base pairs and used single-molecule approaches to assess the structure targeted by ribosomes. We found that the first ribosome target stem was resistant to unwinding when the neighboring loop was confined along the stem; such constrained conformation was dependent on the presence of consecutive adenosines in this loop. Mutations that disrupted the distal base triples abolished all remaining tertiary base pairs. Changes in frameshifting efficiency correlated with the stem unwinding resistance. Our results demonstrate that various tertiary base pairs are coordinated inside a highly efficient frameshift-stimulating RNA pseudoknot and suggest a mechanism by which mechanical resistance of the pseudoknot may persistently act on translocating ribosomes.